2014
DOI: 10.1017/s0950268814001721
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR in the diagnosis of canine leishmaniasis in two different epidemiological regions: Campinas (SP) and Teresina (PI), Brazil

Abstract: SUMMARY Using the polymerase chain reaction (PCR) test for diagnosis of canine leishmaniasis has greater sensitivity and specificity than culture and visualization of the parasite. This study compares PCR for the diagnosis of the genus and species of Leishmania with serological techniques used for the control of canine visceral leishmaniasis (CVL) in Brazil, considering two regions. We analysed peripheral blood samples collected from 195 dogs in the Campinas (SP) and Teresina (PI) regions. ELISA was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The low accuracy found in serological tests (DPP and ELISA) confirms the necessity of better confirmatory laboratory methods, mainly due to the low parasite load and low levels of anti- Leishmania antibody in asymptomatic dogs. Therefore, when the clinical and serological tests are negative, real-time PCR can be used as an alternative [14, 15, 34, 35]. In the agreement, Grimaldi et al [12] found that the DPP ® rapid test for CVL presented high sensitivity (98%) to identify symptomatic dogs and low sensitivity (47%) to asymptomatic dogs in areas free of VL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low accuracy found in serological tests (DPP and ELISA) confirms the necessity of better confirmatory laboratory methods, mainly due to the low parasite load and low levels of anti- Leishmania antibody in asymptomatic dogs. Therefore, when the clinical and serological tests are negative, real-time PCR can be used as an alternative [14, 15, 34, 35]. In the agreement, Grimaldi et al [12] found that the DPP ® rapid test for CVL presented high sensitivity (98%) to identify symptomatic dogs and low sensitivity (47%) to asymptomatic dogs in areas free of VL.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is hardly accepted by the owners of the animals and the studies are controversial in relation to its effectiveness. Therefore, the diagnosis of CVL must be highly accurate, avoiding unnecessary euthanasia [14, 15]. Although a variety of tests including serological, parasitological and molecular methods are available, the diagnosis of CVL is still unsatisfactory [1416].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in experimental rodent model (McCulloch et al, 2009) and Leishmania spp. in dogs (Costa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PCR has been performed for the diagnosis of CVL, with its potential for parasite detection showing high levels of sensitivity and specificity 27 , and no signifi cant difference has been reported for samples obtained from canine peripheral blood, bone marrow, and skin fragments 28 . The presence of CVL-positive dogs in Mossoró should concern local authorities because dogs are the primary domestic reservoir for human disease in urban areas 29 .…”
Section: Factors Associated With the Reservoirmentioning
confidence: 99%